ANALYSIS OF RISK STATUS, KNOWLEDGE LEVEL, AND LEVEL OF OBEDIENCE ABOUT COVID-19 IN THE COMMUNITY IN JIMBARAN SUBDISTRICT - Irawan, Angeline Aprilia; Tanaya, Rena Alfreda; Ratana, Dhamma; Kuswana, Rynov; Suarsana, I Nyoman (Buletin Udayana Mengabdi; Vol 19 No 4 (2020): Buletin Udayana Mengabdi, 2020)
Coronavirus Disease 2019 is an infectious disease caused by a new type of coronavirus. The virus spreads quickly and causes a highly diverse range of clinical manifestations. Because of that, some serious actions are needed to stop chains of transmission. Many government acts can’t stop the spreading of the virus itself if the people’s knowledge and obedience about the virus are poor. This research aims to know about risk status, knowledge level, and level of obedience of the people in Jimbaran subdistrict about Coronavirus Disease 2019. The method that is used is an online questionnaire that is distributed to the community. The result showing most of people’s having a low risk, high knowledge level, and great obedience about the virus. This result can be useful for taking the next decision to break the chains of Coronavirus Disease 2019 transmission, especially in the Jimbaran subdistrict.